Analisis Unjuk Kerja dan Desain Jaringan Komputer Menggunakan Metode Top-Down Network Desain pada Jurusan Teknik Elektro Politeknik Negeri Pontianak - Neny Firdyanti; Muhammad Hasbi; Widda Arifa (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2021)
Implementation of the Teaching and Learning Process in the Department of Electrical Engineering Pontianak State Polytechnic uses internet services as a support tool. However, it is often found that access slows down and is suddenly cut off. Therefore it is necessary to carry out an analysis that includes the aspects of performance and design. This study uses the Top-Down Network Design Method, which has 3 stages, namely Identifying Needs which include Business Analysis, Technical Analysis, Network Characteristics Analysis, and Network Traffic Analysis. Then Network Logic Design which includes Network Topology Design, IP Address Allocation Design, Selection of Switching and Routing Protocols, Forming a Network Security Strategy, and Forming a Network Management Strategy. The last one is the Physical Network Design which refers to the network logic design that has been made, then the selection of technology and equipment will be applied to the network design that will be produced in this study. In this study, the calculation and analysis of parameters such as delay, jitter, bandwidth, utilization, packet loss and throughput will be carried out using the iperf and Wireshark applications.